Effectiveness of freedom of movement during first stage of labour - Dr. M.VAIJAYANTHIMALA Ph.D (International Journal of Pharma and Bio Sciences, 2017)
Today, in modern obstetrics immobility as become common occurrence during labour due to risk focused management and most of the child birth is managed by the ‘Active Management’ of labour with many interventions. Natural Birth’ generated with “Freedom Of Movement” considered as a very effective intervention to enhance the birth outcome. An experimental study was conducted among 211 primi parturient mothers who were in active stage of labour with uncomplicated pregnancy were allocated to experimental group (n=106) and control group (n=105) by using simple random sampling technique. Maternal outcome mean score among the study group primi parturient mothers was 27.99 whereas in control group it was 22.58 and the difference was 5.41 score with the calculated ‘t’ value was 10.77 at p=0.001 level In study group fetal outcome mean score was 16.41 whereas in control group it was 14.47 and the obtained ‘t’value is 6.49 at p=0.001 level. There was high statistical significance found in maternal and fetal outcome between study and control group which shows that the freedom of movement intervention enhances birth outcome among the primi parturient mothers.